Long-term monitoring reveals the success of salmonid habitat restoration - Louhi, Pauliina; Vehanen, Teppo; Huusko, Ari; Mäki-Petäys, Aki; Muotka, Timo (Canadian Journal of Fisheries and Aquatic Sciences, 2016)
The growing concern on declining salmonid populations has resulted in numerous restoration projects with variable responses worldwide. In this spatially replicated multiyear study, we assessed the long-term (12 years postrestoration) effects of in-stream habitat restoration (i.e., addition of boulders or large woody debris (LWD) together with boulders) on densities of three age-classes of juvenile brown trout (Salmo trutta) in six forest streams in northern Finland. LWD combined with boulders was more beneficial, particularly for the larger trout (age-2 and older), than were boulder structures alone, indicating that the more diverse habitat created by LWD may have provided a safeguard against drought for the larger fish. Density of age-0+ trout showed a significant long-term increase in boulder-restored sections, providing evidence that log structures may need to be complemented by stony enhancement structures to guarantee the availability of suitable stream habitat for all trout age-classes. As trout densities are known to exhibit inherently wide interannual variability that tracks climatically induced hydrological variation, long-term postrestoration monitoring that encompasses extreme hydrological events is critical for evaluating the success of restoration projects.